Deciphering the Molecular Mechanisms of Cancer: Role of Proto-Oncogenes and Targeted Therapies (Asian Journal of Pharmaceutics (AJP), 2025)
Cancer is a multifaceted disease characterized by uncontrolled cell growth, invasion, and metastasis. At themolecular level, proto-oncogenes play a critical role in normal cell growth and differentiation. However, theirconversion into oncogenes due to mutations or overexpression can drive tumorigenesis. This review delves intothe molecular transformation of proto-oncogenes into oncogenes and the underlying causes, including geneticmutations, chromosomal abnormalities, and viral infections. In addition, we explore the significance of tumorsuppressor genes in counteracting oncogenic signals and their role in maintaining cellular integrity. Advancementsin cancer research have led to the development of targeted therapies that specifically inhibit oncogene-drivenmalignancies. Initially, oncogene-targeted drugs such as Herceptin, gefitinib, and STI-571, along with monoclonalantibodies, have revolutionized cancer treatment by disrupting tumor-promoting pathways while minimizingdamage to normal cells. Furthermore, recent developments in oncogene-directed therapies are paving the wayfor precision medicine in oncology. By understanding the molecular basis of cancer, researchers can developinnovative therapeutic strategies to combat malignancies at their roots. This review highlights the importanceof proto-oncogene regulation, oncogene inhibition, and emerging targeted therapies in the fight against cancer,offering insights into future directions in molecular oncology.